The influence of the support on the singlet oxygen quantum yields of porphyrin supported photosensitizers - Pineiro, Marta (2009)
A halogenated porphyrin was covalently supported on aminoalkylated silica and aminoalkylated Merrifield polymer through a chlorosulfonation reaction. The supported porphyrin was tested for the photoxidation of α-terpinene. The kinetics of photocatalysis were evaluated using 9,10-dimethylanthracene as target and singlet oxygen formation quantum yield was calculated. The influence of the support, silica, Merrifield and other polymers, on the quenching of singlet oxygen were also evaluated.